(3GdLhGgQ GdHgjI aj TQM GdSjQI GdfHhjIs - (3Ydj Hf eMeO Hf YHO GdQMef Hf Ydj, CHh GdEQTGO, fhQ GdOjf GdCLghQj,J (B1066 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg KbJi (B: (3jbhd QGLi ef Zdg GdegQH YHO GdQMje Hf GdMSjf GdePfH jbhd QGLi (B: (3GdQLGdI eYjfGf CMOgeG GdCed aGdQGLi GdBed hefg bhdg JYGdi jQLhf QMeJg hGdGKfi GdNha hefg hGQLh Gdjhe GdBNQ aGdQGLi HeYfi GdNGja hheefg jfTC Gs
(3BNQgG (B:s
(3eJBcd hBNQ GdehLhO efgG (B: (3fYeG HVe Gdfhf hcSQ GdYjf G deTOOI hCdag ddJTfjf ef GdfYeI HGdaJM Ci GdeSQI Zdi fYegeG Gddg HfYeI bGdg GdTGQM hgPG NdGa eG PcQg TQGM GdQSGdI ef Cf Gd fYeI HGdaJM GdJfYe hHGdcSQ eG ,Ye Ydi GdYHO Hg hHGdVe GdSQhQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eYfhfI HGdMHQ GdCMeQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B13 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B207s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs